Archaeologies of indigenous presence / edited by Tsim D. Schneider and Lee M. Panich.
"Challenging narratives of Indigenous cultural loss and disappearance, This book highlights collaborative archaeological research and efforts to center the enduring histories of Native peoples in North America through case studies from several regions across the continent"-- |c Provided by publisher.